Implementasi Sistem Pengaduan Warga Sekitar Untuk Melaporkan Berbagai Masalah Berbasis Web Dengan Metode RAD (Studi Kasus : Desa Cijantra) - Hanif Sandi Wardana; Muhammad Yasser Arafat (CV. Multi Kreasi Media, 2025)
The development of information technology opens opportunities to improve public services, including handling community complaints. Cijantra Village requires an online complaint system to enable residents to report issues efficiently and transparently. This project develops such a system using Rapid Application Development (RAD), which emphasizes iterative processes and user involvement for faster results. The system provides features such as report submission, status tracking, complaint data management, and follow-up notifications. Implementation shows that the system helps residents submit complaints systematically and assists officials in responding effectively, thereby improving transparency, efficiency, and service quality in Cijantra Village.